Narrative in drama : the art of the Euripidean messenger-speech - Jong, Irene J. F. de. (Mnemosyne, Supplements, 1991)
This book, consisting of three self-contained studies, deals with the Euripidean messenger-speech. The first study concerns the form of the messenger-speech, which is that of a first-person narrative, and the consequences of this form. The second study analyses the messenger's style of presentation. In the third study the place and function of the messenger-speech within the play is discussed. Although scholars have dealt with the messenger-speech before, there is no single, up-to-date work of reference available. The present study aims at filling this void, while making use of analytical tools deriving from narratology and drama-theory. Eight appendices are added, which provide the reader with complete lists of phenomena discussed in the main text. Often considered transparent and self-explanatory, the messenger-speeches are now shown to be both complex and subtle texts.